Finding Our Bearings in Post-method Waters - Littlewood, William; Wang, Shufang (Frontiers in Psychology, 2022)
This paper proposes a framework to guide us in designing and implementing our personal classroom language pedagogy. It is based on three major principles which the teacher can keep constantly in mind: that the learners need to be engaged, that the language needs to be memorized, and that learning needs to move towards communicative competence. Each principle generates between two and four dimensions which the teacher can use to develop specific strategies. The principle of engagement draws us to attend to the behavioural, social, emotional and cognitive dimensions which are intertwined in classroom learning. The principle of memorization highlights the importance of two key concepts in the study of memory: depth of processing and practice (especially distributed practice). Orientation to communication requires us to make a principled selection of learning activities according to whether they focus on forms, meanings, messages, or communicative interaction. These ten principles and dimensions reflect the theoretical underpinnings of learning in general and the nature of communicative language use. Based on them, each teacher can conduct his or her personal, contextualised search for bearings in the waters of post-method language pedagogy.